I need some help solving the following: a) (2)*3^x = (7)*5^x b) 12^x = (4)*8^(2x) c)(12)*6^(2x-1) = 11^(x+3) d) (7)*0.43^(2x) = (9)*6^(-x) Thanks.
Follow Math Help Forum on Facebook and Google+
Originally Posted by andymac I need some help solving the following: a) (2)*3^x = (7)*5^x b) 12^x = (4)*8^(2x) c)(12)*6^(2x-1) = 11^(x+3) d) (7)*0.43^(2x) = (9)*6^(-x) Thanks. Two methods for these. I will show you both for the first problem and you can apply it to the rest Method one taking the natural log of both sides gives Algebraically manipulating gives so Method two through manipulation we get taking the natural log of both sides gives
View Tag Cloud